PENGARUH CAPITAL INTENCITY RATIO, SIZE, EARNING PER SHARE EPS, DEBT TO EQUITY RATIO, DIVIDEN PAYOUT RATIO TERHADAP MANAJEMEN LABA - Aprih Santoso; Diana Puspitasari; Rahmatya Widyaswati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2016)
The financial statements are the means of communicating financial information to parties outside the company. In preparing the financial statements, accrual basis chosen for a more rational and fair in reflecting the real financial condition of the company, but on the other hand the use of the accrual basis may provide more flexibility to the management in selecting the method of accounting for not deviate from the rules of the Financial Accounting Standards applicable. Selection of accounting methods that are deliberately selected by management for a particular purpose known as earnings management.This study replicates previous research on earnings management. Financial variables used in this study and is thought to have an effect on earnings management in this study is the Capital Intencity Ratio (CIR), firm size (SIZE), Earning Per Share (EPS), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR). The purpose of this study is to see the effect of Intencity Capital Ratio (CIR), firm size (SIZE), Earning Per Share (EPS), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) of the Income Management. The sample in this study were taken by purposive sampling, with specific criteria that the Company manufacturing sector food beverage that go public in Indonesia is not doing mergers and acquisitions during the period of the study, had a positive net income and present the complete financial statements, as well as presenting the ratio of the complete suite the variables to be studied, during the period 2010-2014. Thus obtained a sample of 10 companies.During the period show that the study data were normally distributed. Based normality test, multicollinearity, heteroscedasticity test and autocorrelation test found no deviation from the classical assumptions. It shows the available data has been qualified using multiple linear regression model. The results showed that the only variable Intencity Capital Ratio (CIR) and Earning Per Share (EPS) showed a significant effect on Earnings Management. Whereas the variable firm size (SIZE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) did not show any effect on Earnings Management. The predictive ability of these variables on the seventh Earnings Changes in the study by 39 percent, while the remaining 61 percent is affected by other factors that are not included in the research model.